2001
DOI: 10.1002/eat.1044
|View full text |Cite
|
Sign up to set email alerts
|

Total energy expenditure as measured by doubly‐labeled water in outpatients with bulimia nervosa

Abstract: This finding of normal TEE in symptomatic outpatients with bulimia nervosa is consistent with a previous study that found no difference in TEE in a sample of symptomatic inpatients with bulimia nervosa. These data suggest that the energy conserving metabolic adaptations characteristic of semi-starvation do not occur in patients with bulimia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Two studies measured TEE using the DLW method and did not find a difference between outpatients and inpatients with BN and controls (Kotler, Devlin, Matthews, & Walsh, 2001;Pirke et al, 1991).…”
Section: Teementioning
confidence: 98%
“…Two studies measured TEE using the DLW method and did not find a difference between outpatients and inpatients with BN and controls (Kotler, Devlin, Matthews, & Walsh, 2001;Pirke et al, 1991).…”
Section: Teementioning
confidence: 98%
“…This lack of objective measurement provides weak evidence for the prevalence of excessive exercise in eating disorder patients (Solenberger, 2001). In comparison, studies using objective measures of exercise fail to find elevated exercise levels in eating disordered groups compared to control groups (Bouten, van Marken Lichtenbelt, & Westerderp, 1996;Einerson, Ward, & Hanson, 1988;Kotler, Devlin, Matthews, & Walsh, 2001). Finally, studies have found low aerobic fitness levels (using maximal exercise testing) in anorexia nervosa patients (Rowland, Koenigs, & Miller, 2003), which suggests that they may not be exercising to excess.…”
mentioning
confidence: 99%
“…The 42 normal controls were participants in other studies conducted at the Eating Disorder Research Unit at the New York State Psychiatric Institute during the time of the treatment study (Kissileff et al, 1996;Devlin et al, 1997;Kotler, Devlin, Matthews, & Matthews, 2001). To participate in these studies, subjects were required to be women between the ages of 18 and 45 whose weights were between 80% and 120% of ideal body weight.…”
Section: Controlsmentioning
confidence: 99%